2010
DOI: 10.1007/s10519-010-9379-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype on the Pigmentation Regulating PMEL17 Gene Affects Behavior in Chickens Raised Without Physical Contact with Conspecifics

Abstract: Chickens homozygous for the Dominant white or wild-type allele of PMEL17 were subjected to a broad phenotyping in order to detect consistent differences between genotypes. To exclude feather pecking, the chickens were individually housed without physical contact, from the day of hatching, and tested for social, aggressive, fear and exploratory behaviors, and costicosterone and testosterone levels were assessed. In a principal component analysis, 53.2% of the behavior variation was explained by two factors. Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It was suggested either that the mutation could have been selected because it conveyed a better ability to stay fit under crowded conditions, by not eliciting feather pecking to the same extent, or that it might have pleiotropic effects on other behavior, which made the individuals carrying the mutation less exposed. We subsequently found that the mutation was related to differences in social and exploratory behavior, and also when the birds were raised without the opportunity to interact physically with conspecifics (60)(61)(62), where pigmented birds tended to be more aggressive and explorative ( Figure 4). This shows a clear pleiotropic effect on behavior of a specific pigment-related mutation, but it is of course not possible to conclude anything regarding which phenotype was originally selected on.…”
Section: Pleiotropy In Genes Controlling Pigmentationmentioning
confidence: 93%
“…It was suggested either that the mutation could have been selected because it conveyed a better ability to stay fit under crowded conditions, by not eliciting feather pecking to the same extent, or that it might have pleiotropic effects on other behavior, which made the individuals carrying the mutation less exposed. We subsequently found that the mutation was related to differences in social and exploratory behavior, and also when the birds were raised without the opportunity to interact physically with conspecifics (60)(61)(62), where pigmented birds tended to be more aggressive and explorative ( Figure 4). This shows a clear pleiotropic effect on behavior of a specific pigment-related mutation, but it is of course not possible to conclude anything regarding which phenotype was originally selected on.…”
Section: Pleiotropy In Genes Controlling Pigmentationmentioning
confidence: 93%
“…This gene encodes a melanocyte-specific protein, essential for maturation of melanosomes, and the identified domesticated mutation inhibits all expression of black pigment in the bird. It turned out that the mutation not only causes a white plumage, and reduces the risk of being the target of feather pecking, but also has pleiotropic effects on exploration and aggression (Karlsson et al, 2010;Karlsson et al, 2011). …”
Section: Behavioural Genesmentioning
confidence: 99%
“…A 9 bp insertion in exon 10 acts in a dominant fashion, such that birds homozygous for the ancestral junglefowl allele (i) are black, whereas those carrying the White Leghorn allele (I) are white (heterozygotes sometimes have minor pigmentation). It has been demonstrated that there are substantial behavioural differences between birds carrying the junglefowl and White Leghorn alleles, such that i/i individuals birds are more vocal, have lower activity levels in a test measuring fear of humans, and are more aggressive, social and explorative [46][47][48] than I/I birds, suggesting either that PMEL17 has pleiotropic effects on behaviour or the existence of a closely linked behavioural locus [48]. This locus may also be associated with feather-pecking, a bullying behaviour that can result in severe damage to the victim [49].…”
Section: (D) Extended Homozygosity Approachesmentioning
confidence: 99%